EXCHANGE MARKET PRESSURE INDEX AS A MACROECONOMIC RISK MEASURING INSTRUMENT - COLESNICOVA, Tatiana; PERCIUN, Rodica; TVIRCUN, Alexandra (Economy and Sociology, 2021)
The financial sector of the Republic of Moldova belongs to the developing ones and is characterized by a higher level of risk and, therefore, a higher likelihood of a systemic crisis. Globalization and development of advanced information technologies not only create great opportunities for rapid economic development, but also pose serious security threats to the economic development of states, especially in a developing economy. In these conditions, the issue of ensuring the financial stability of the state is becoming increasingly relevant. The state of the financial and foreign exchange market represents one of the most important aspects of the financial security of the state. This study has been developed as part of the scientific project 15.817.06.02A “Development of tools for measuring the financial stability of the state”. The study analyzes various macrofinancial risk management tools. The purpose of this study was to calculate the pressure index on the foreign exchange market of both the Republic of Moldova and the main partner countries in terms of international trade. The results of related studies conducted by the authors of this work, which revealed that stability indicators in the foreign exchange market are associated with foreign trade risks served as an argument for the authors of the work to calculate the pressure index on the currency market of Romania and the Russian Federation for comparison with the indicators of the Republic of Moldova. Methods used in research include theoretical and comparative approaches, descriptive statistics and econometric models. The results of the research showed that international trade and the foreign exchange market are interdependent. The first can be considered a channel for transmitting the currency crisis, since demand increases with increasing imports, and this leads to increased pressure on the foreign exchange market. Increased exports reduce pressure on the foreign exchange market. But the greatest impact on the foreign exchange market in the Republic of Moldova is made by remittances from abroad, which are directly correlated with the dynamics of labor exports. At the same time, it was concluded that at present, due to macroprudential regulation, there are no linear dependencies in financial markets and, therefore, there are no correlations, but only the interdependence of variables.